Comportamento de camundongos Suíços frente à infecção por Leishmania (V.) braziliensis e/ou Leishmania (L.) amazonensis. - Rocha, Juliana da Câmara (2014)
Leishmaniasis are diseases caused by different species of parasites in the genus Leishmania. Isogenous mice are widely used in the investigation of immunopathological processes associated with these diseases. However, there are few studies of experimental leishmaniasis with heterogeneous mice with a diverted genetic makeup are few. This work evaluated the behavior of heterogeneous Swiss mice infected with the species L. (V.) braziliensis and/or L. (L.) amazonensis. Initially, the Swiss mice were infected in the paw with the promastigote stage of L. braziliensis and L. amazonensis singly; the progression of the wound was monitored for nine weeks, and the parasitic load and the levels of the cytokines IFN-γ, TFN-α, and NO were measured. After six and seventeen weeks, the Swiss mice previously coinfected with L. braziliensis were infected in the other paw with L. amazonensis; The progression of the infection was analyzed. At the eighth or ninth weeks following the double infection, the parasitic load, the levels of cytokine IFN-γ, TNF-α, and NO in cells of the spleen and the popliteal lymph node were determined. Infected mice with L. braziliensis developed a small wound at the site of infection (0,26 ± 0,05 mm). However, the infection remained unaltered without traces of progression and without detection of parasites in the spleen, but showed an increase in the levels of IFN-γ in cells of the spleen. Conversely, the Swiss mice infected with L. amazonensis developed wounds with continuous and progressive growth, with the presence of parasites in the spleen in spite of a significant increase in the synthesis of IFN-γ. With respect to doubly infected animals, the wound in the site of the infection by L. amazonensis also presented a progressive growth. However, from the second week the wounds in these animals were significantly smaller than the wounds in the animals infected only with L. amazonensis. In the eighth week of assessment, a difference in the size of the wound (2,54 ± 0,57 mm) between these last two groups of animals was observed. This decrease in the wounds size correlated with increased levels of IFN- γ and NO in the spleen cells in the animals doubly infected. With the obtained results, it can be concluded that Swiss mice develop a phenotype of susceptibility to infection by L. amazonensis. Moreover, the previous infection with L. braziliensis confers a partial protection against L. amazonensis associated with a large production of IFN-γ.